Ambient temperature effect on Amorphous Silicon (A-Si) Photovoltaic module using sensing technology - Zahurul S.; Mariun N.; Othman M.L.; Hizam H.; Abidin I.Z.; Toudeshki A. (IEEE Computer Society, 2023)
Efficiency; Photovoltaic cells; Photovoltaic effects; Silicon compounds; Solar power generation; Solar radiation; Temperature; Thermal effects; Amorphous silicon (a-Si); Comparison analysis; Electrical performance; Operating temperature; Photovoltaic modules; Radiation coefficient; Sensing technology; Temperature coefficient; Amorphous silicon